Automated Web Based System for Bone Age Assessment using Histogram Technique - Mansourvar, Marjan; Raj, Ram Gopal; Ismail, Maizatul Akmar; Abdul Kareem, Sameem; Shanmugam, Saravanan; Wahid, Shahrom; Mahmud, Rohana; Hj. Abdullah, Rukaini; Nasaruddin, Fariza Hanum Fariza; Idris, Norisma (Malaysian Journal of Computer Science, 2012)
Bone age assessment (BAA) is often used to evaluate the growth status of children as part of the detection of hormonal problems and genetic disorders. The determination of skeletal maturity is done based on a radiological examination of the hand-wrist skeletal area.This paper introduces a novel approach for BAA that utilizes a histogram based comparison technique. This approach is executed as a web based system that uses an image repository and similarity measures based on content-based image retrieval. This study aims to overcome to the limitations of traditional methods utilized to estimate human age which were often imprecise.The system provides age prediction for hand and wrist x-ray images up till age of 18 years. The results of the system evaluation indicate this method as a reliable method for BAA with the error rates of -0.170625 years compared with BoneXpert system that have returned error rate of between Â±0.46 to Â±0.37 years.